2009
DOI: 10.1080/00288230909510525
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for assessing the salt tolerance of lucerne (Medicago sativaL.) cultivar seedlings by combining agronomic and physiological indicators

Abstract: Salinisation caused by irrigation is threatening the forage yield of lucerne pasture in the arid and semi-arid areas of west China. To select lucerne cultivars with good salt tolerance, the relative salt tolerance of five lucerne cultivars was assessed based upon shoot dry weight, shoot KV Na + ratio, leaf malondialdehyde (MDA) content and relative membrane permeability (RMP) at the seedling stage. NaCl reduced the shoot dry weight and shoot K + /Na + ratio, and enhanced the leaf MDA content and RMP in all cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Morphological symptoms, biochemical and physiological responses of the wheat genotypes revealed that stress treatment with 200 mM NaCl for 14 days was most appropriate for comparative evaluation of the wheat genotypes ( Figure 1 and Supplementary Table S1). The available literature corroborated our finding as we found that 200 mM NaCl has been commonly used for evaluation of salt tolerance of different plant species including wheat (Tammam et al, 2008; Bao et al, 2009; Wu et al, 2013). Hence, salt treatment with 200 mM NaCl for 14 days was used in the subsequent experiments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Morphological symptoms, biochemical and physiological responses of the wheat genotypes revealed that stress treatment with 200 mM NaCl for 14 days was most appropriate for comparative evaluation of the wheat genotypes ( Figure 1 and Supplementary Table S1). The available literature corroborated our finding as we found that 200 mM NaCl has been commonly used for evaluation of salt tolerance of different plant species including wheat (Tammam et al, 2008; Bao et al, 2009; Wu et al, 2013). Hence, salt treatment with 200 mM NaCl for 14 days was used in the subsequent experiments.…”
Section: Discussionsupporting
confidence: 89%
“…Relative value for the indicator in shoot and root was calculated from treatment (200 mM NaCl) mean values as percentages of the respective mean value under control condition (0 mM NaCl). The relative value for each of these parameters was then standardized according to the formulas given by Bao et al (2009); one for the indicators which are positively correlated (proline, soluble sugar, TPCs, and antioxidant potential) with salt tolerance [X′ ij = (X ij – X jmin )/(X jmax – X jmin )], and another for the indicators which are negatively correlated (DW, lipid peroxidation, Na + /K + ratio, and total chlorophyll content) with salt tolerance [X′ ij = 1 - (X ij – X jmin )/(X jmax – X jmin )]. Herein X′ ij = 0, when X ij = X jmin ; and X′ ij = 1, when X ij = X jmax .…”
Section: Methodsmentioning
confidence: 99%
“…where X ij is the j indicator value of i cultivar, X jmin is the minimum value of the j indicator and X jmax is the maximum value of the j indicator (Bao et al 2009;Wu et al 2013). The relative drought tolerance of sugar beet cultivars was then determined from fresh weight, water content, Na + and K + concentrations, Na + /K + ratio, and proline and sugar concentrations in the present study, presented as the following equation (Bao et al 2009;Wu et al 2013):…”
Section: Determination Of Osmotic Potential (ψ S ) and Calculation Ofmentioning
confidence: 99%
“…The relative drought tolerance of sugar beet cultivars was then determined from fresh weight, water content, Na + and K + concentrations, Na + /K + ratio, and proline and sugar concentrations in the present study, presented as the following equation (Bao et al 2009;Wu et al 2013):…”
Section: Determination Of Osmotic Potential (ψ S ) and Calculation Ofmentioning
confidence: 99%
“…High biomass production, high nutritional quality and widespread adaptability have made alfalfa as a leading forage crop with a good fame of ‘Queen of the Forages’ (Bao et al, 2009; Kumar, 2011). As an economically important legume forage crop, alfalfa has brought considerable profits for local people and companies in northern China.…”
Section: Introductionmentioning
confidence: 99%